1995
DOI: 10.1530/jrf.0.1030063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hormonal and histological changes during follicular growth, as measured by ultrasonography, in cattle

Abstract: The aim of the study was to compare histological and endocrinological indices of ovarian follicle health in cattle with monitoring of follicle growth and regression by ultrasound imaging in vivo. Ultrasound scanning was performed daily. Follicles were obtained at ovariectomy; follicular fluid was collected for assay, and the degree of atresia was assessed histologically. Histological atresia was correlated with growth patterns when anovulatory growing and regressing follicles were compared (P < 0.05), but was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 0 publications
3
38
0
1
Order By: Relevance
“…Oestradiol was measured in conditioned medium without extraction (Price et al 1995). Inter-and intra-assay coefficients of variation were 12 and 10% respectively.…”
Section: Assaysmentioning
confidence: 99%
“…Oestradiol was measured in conditioned medium without extraction (Price et al 1995). Inter-and intra-assay coefficients of variation were 12 and 10% respectively.…”
Section: Assaysmentioning
confidence: 99%
“…100 ng progesterone/ml were classified as atretic (n ¼ 4). These represent mature dominant growing, static and regressing follicles respectively (Price et al 1995). Cross-contamination of theca and granulosa cells was tested by detection of mRNA encoding cytochromes P450 aromatase (Cyp19) and 17a-hydroxylase (Cyp17) in each sample by PCR (Buratini et al 2005).…”
Section: Tissue Collectionmentioning
confidence: 99%
“…Concentrations of estradiol and progesterone in FF from Experiment 3 were analyzed by RIA using double antibody precipitation and charcoal absorption methods, as validated for use with bovine FF (Carrière & Lee 1994, Price et al 1995. Spiking FF samples with 2 pg/tube and 5 pg/tube of estradiol gave 81 and 107% recovery respectively.…”
Section: Steroid Assaysmentioning
confidence: 99%
“…Nonatretic follicles contain higher oestradiol and lower progesterone concentrations than do atretic follicles (Ireland and Roche, 1983;Richards and Kirdich, 1984;Blödow et al, 1988). Other studies indicate that static follicles, containing lower oestradiol concentrations, may not all be truly atretic (Price et al, 1995). It was also shown that histological results did not correlate well with the stage of follicular growth or regression as determined either in vivo by ultrasound scanning of ovaries or by assessment of follicular concentrations of oestradiol, progesterone or inhibin.…”
Section: Abstract: Follicle Steroids Redox Potential Cell Injury mentioning
confidence: 97%
“…In addition, morphologically and clinically healthy follicles are characterised by several visible indices (Moor et al, 1978;McNatty et al, 1984;Fortune, 1994). Histological studies have defined Acta Veterinaria Hungarica 54, 2006 several degrees of atresia based on pyknotic nuclei, thickness of granulosa cell layers and membrane integrity (Price et al, 1995;Blondin et al, 1996;Zeuner et al, 2003). Determination of hormonal concentrations in the follicular fluid is also used to indicate the health status of follicles.…”
Section: Abstract: Follicle Steroids Redox Potential Cell Injury mentioning
confidence: 99%